Through thick and thin: data commons, community and the struggle for collective data governance - Tommaso Fia; Gijs van Maanen (Technology and Regulation)
Collective data governance mechanisms such as data commons have recently gained traction in both theoretical and policy-oriented discussions as promising alternatives to the shortcomings of individualistic data protection and data markets. Many of these approaches centre around the idea of community as the key social institution overcoming these limitations. Yet, far less attention has been paid to the meaning, features and implications that the language of community can have for data commons.